Fludarabine/Cyclophosphamide Conditioning Regimen in Aplastic Anemia Patients Receiving Matched-Sibling Donor Transplant Is Non-inferior to ATG/Cyclophosphamide: A Single-Center Experience from Pakistan - Uzma Zaidi; Mushkbar Fatima; Shafaq Abdul Samad; Kashif Shafique; Hira Fatima Waseem; Tasneem Farzana; Tahir Sultan Shamsi (Hindawi Limited, 2022)
The successful outcome of allogeneic hematopoietic stem cell transplant (HSCT) in aplastic anemia patients is driven by suitable donor selection, appropriate conditioning regimen, early intervention, and optimal supportive care after transplant. Pakistan, being a developing country, faces grave economic challenges due to meager health care budget; therefore, cost constraints remain the foremost impediment in optimizing transplant facilities for socioeconomically deprived patients. We conducted a single-center retrospective analysis of aplastic anemia patients (N=130), who received matched sibling donor transplants from 2011 to 2019, treated with either fludarabine/cyclophosphamide (Flu/Cy) or antithymocyte globulin/cyclophosphamide (ATG/CY) conditioning regimen. Median age was 16 years (IQR, 11-20), and it ranged from 3 to 48 years. The median time from diagnosis to transplant was 3 months (IQR, 2 to 4), and it ranged from 1 to 8 months. The estimated overall survival (OS), relapse-free survival (RFS), and GvHD-free survival (GFS) were found to be 69.0%, 66.7%, and 64.3% in the ATG/Cy group while 76.1%, 72.7%, and 62.5% in the Flu/Cy group, respectively, after a median follow-up of 30 months (IQR, 8 to 55), and it ranged from 0 to 98 months for the study groups. The Flu/Cy regimen was well tolerated and was not associated with increased risk of GvHD. Hence, it may be an appropriate alternative conditioning regimen for developing countries with limited health care resources.